Women Derivative Names with Suffix -Чиц (А) / -Щиц(А) in the Russian Media Space - GUZAEROVA, R.R.; KOSOVA, V.A.; GUZI, L. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to functioning in the modern russian language word-formation type with the suffix -чиц (а)/-щиц (а) as a means of expressing the derivational category of femininity. The language material of the study is represented by 459 lexemes with the suffix -чиц (а)/-щиц (а), functioning in modern contexts. The semantic and stylistic characteristics of the considered word-formation type are given. The conclusion is made about the productivity and universality of the feminitives -чиц (а)/-щиц (а) in modern Russian, which allows them to remain in the center of the word-formation category of femininity. RESUMEN El artículo está dedicado a funcionar en el tipo moderno de formación de palabras en ruso con el sufijo –чиц (а) / - щиц (а) como un medio para expresar la categoría derivada de la feminidad. El material lingüístico del estudio está representado por 459 lexemas con el sufijo –чиц (а) / - щиц (а), que funciona en contextos modernos. Se dan las características semánticas y estilísticas del tipo considerado de formación de palabras. Se llega a la conclusión sobre la productividad y la universalidad de las feminitivas –чиц (а) / - щиц (а) en el ruso moderno, lo que les permite permanecer en el centro de la categoría de feminidad de formación de palabras.